Differences in Mathematical Adaptive Reasoning Abilities and Productive Struggle Achievement Through Problem-Based Learning - Siti Masitoh; Tatang Herman; Aan Hasanah (FKIP Universitas Lampung, 2024)
The low adaptive reasoning abilities and productive struggle of junior high school students in learning mathematics drive this study. The research aims to determine whether there are differences in adaptive reasoning abilities and the achievement of productive struggle between students using problem-based learning and direct instruction. This research uses a quasi- experimental design with a pre-test-post-test control group design. The population consists of all seventh-grade students from a junior high school in Bandung. The sample includes class VII-B, with 31 students as the control group using the direct instruction model, and class VII-K, with 26 students as the experimental group using the problem-based learning model. The sampling method employe dis purposive sampling. The research instruments include an adaptive reasoning ability test and a productive struggle scale questionnaire. Data is analyzed both descriptively and inferentially. The results show that: (1) There is a significant difference in adaptive reasoning abilities between students using problem-based learning and those using direct learning. (2) There is no difference in the achievement of the productive struggle between students using the different learning models. This research concludes that problem-based learning can have a positive impact on adaptive reasoning abilities but does not directly influence the achievement of productive struggle compared to direct learning. Keywords: adaptive reasoning, problem-based learning, productive struggle. DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1037-1050